2006
DOI: 10.1111/j.1525-1438.2006.00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Micrometastases detected by cytokeratin 19 expression in sentinel lymph nodes of patients with early-stage cervical cancer

Abstract: The purpose of this study was to detect micrometastases in sentinel lymph nodes (SLNs) by reverse transcriptase-polymerase chain reaction (RT-PCR) and immunohistochemistry (IHC) analyses for cytokeratin 19 (CK19) expression in early-stage cervical cancer. One hundred twenty-five SLNs were collected from 46 patients with early-stage cervical cancer. Conventional histopathologic techniques revealed 14 metastatic SLNs from 11 out of 46 patients. CK19 expression was detected by RT-PCR and IHC in all the 125 SLNs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 26 publications
2
30
0
3
Order By: Relevance
“…CK19 is the most common diagnostic marker of LN micro-metastasis in gynecological malignant tumors (7,34,35). Our study revealed that, in the primary lesion and metastatic LNs, the positive expression rate of HPA was over 80% and no less than the rate of CK19, which supported the theory that HPA could be a promising biomarker of LN metastasis in cervical cancer.…”
Section: Discussionsupporting
confidence: 82%
“…CK19 is the most common diagnostic marker of LN micro-metastasis in gynecological malignant tumors (7,34,35). Our study revealed that, in the primary lesion and metastatic LNs, the positive expression rate of HPA was over 80% and no less than the rate of CK19, which supported the theory that HPA could be a promising biomarker of LN metastasis in cervical cancer.…”
Section: Discussionsupporting
confidence: 82%
“…The OSNA assay showed 96.2% agreement with 2-mm slice histopathological examination. Wang et al [34] detected micrometastasis using RT-PCR and immunohistochemistry for cytokeratin 19 expression in 46 cervical cancer patients. Both RT-PCR and immunohistochemistry are more sensitive in identifying micrometastasis than conventional pathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CK is still the most commonly applied as monitoring index in studies on micrometastases of cervical cancer. A recent study, in which CK19 was used as an index for detecting micrometastases in sentinal lymph nodes of cervical cancer, by Wang et al (10) found that the detection rates of micrometastases were 42.85 and 20% using PCR and IHC, respectively, and suggested that PCR was more sensitive than IHC. Moreover, Van Trappen et al (4) also noted that 44% of pathologically-negative lymph nodes expressed CK19, and that early micrometastases occured in 50% of patients with cervical cancer.…”
Section: Discussionmentioning
confidence: 99%